International human resource management - Brewstar, Chris (viva books, 2017)
Organizations and enterprises that have a reach across countries around the globe need to be familiar with the cultural differences among nations and how certain issues arising from such factors can be dealt with. In lnternational Human Resource Management, the four authors’ team of Chris Brewster, Paul Sparrow, Guy Vernon and Elizabeth Houldsworth, has put together intense research work to assist those interested and/or involved in comparative and international HRM. This edition is a revised and updated version of the previous, covering the institutional and cultural influences on IHRM. Academics and managers interested in the full range and scope of IHRM should find this text helpful. The topics exclusively covered in this edition are: